Nature-Based Learning Models for Ecological Citizension Formation in Schools - Faujiah, Faujiah; Marzuki, Marzuki (Humaniora: Journal of Indonesia Culture and Society, 2021)
The aim of research was to form students’ ecological citizenship by using a nature-based learning model. Some problems of natural damage such as forest fires, landslides, and floods must be everyone’s concern and responsibility. Therefore, schools needed to prepare a generation who had a responsibility towards nature. The method applied in the research was a descriptive method, while data collection technique was done by means of literature study. Data analysis techniques were in-depth reading to find more accurate data. They were compiled using logical arguments based on the results of analysis. The results of research indicate that forming ecological citizenship in a school environment can be done with environmental knowledge, environmental skills, and environmental ethics. These three aspects can be obtained using a learning model that is in accordance with the basic competencies to be achieved. The learning model that brings students closer to nature is a nature-based learning model outside the classroom that is also adjusted to the basic competencies contained in the Pancasila and Citizenship Education subject. The three aspects of ecological citizenship formation in these schools can be implemented properly if they are socialized to teachers and students. The purpose of this socialization is that teachers can integrate environmental problems into lessons. In contrast, socialization to students is carried out in the hope that an attitude of loving the environment is formed.